INTERAKSI SOSIAL DALAM MEMBANGUN TOLERANSI ANTAR UMAT BERAGAMA DI DUSUN DODOL DESA WONOAGUNG KECAMATAN KASEMBON KABUPATEN MALANG - Syaifudin, Imam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
In religious life can’t be separated with the social interaction, more people who have a different religious background, with the social contact between communities and spiritual values, of course, can build tolerance among religious people. The purpose of this study is to: (1). Describe the pattern of social interaction in developing an understanding of the community in Dodol Hamlet Village Wonoagung District Kasembon (2). Describe the forms of community tolerance Dodol Hamlet Village Wonoagung Kasembon District. To achieve the above objectives, a qualitative research approach with phenomenology is used. The key instrument is the researcher himself, and the data collection techniques used are interviews, observation, and documentation. Data were analyzed using data triangulation technique by digging data from various sources then exposing the data and drawing conclusions. From the results of the study found that the creation of harmony, because of each of the religious adherents of each other open and accept the existence of other religions. The existence of religious diversity that exists in Dodol doesn’t make the interaction between the people of Dodol to be tenuous and rigid, it actually makes its own beauty that can be seen in the pattern of community interaction Dodol citizens. In conducting activities that are social, Dodol people do not consider the majority or minority groups. They always instilled a strong sense of brotherhood and uphold the attitude of mutual help in their society. In relation to building religious tolerance, Dodol people generally have a very dynamic pattern of harmony. This can be seen from the pattern of religious social relations and social relations patterns, which will explain how the pattern of religious harmony that occurred in Dodol Hamlet. In addition, there are also factors that affect the tolerance that occurred in Dodol, namely: family ties, mutual respect, and respect between religious people and mutual help.Keywords: social interaction, tolerance, religious